Respuestas

  • Usuario de Brainly
2013-04-20T22:04:53+02:00

g(0) = 0                  g`1(0) = No existe
g(2) = 1                   g^-1(1) = 2
g(3) = 3/2                g^-1(2) = 1

 

   x                y
----------------------
  0.................0
  1................1/2
  2...............1
  3................3/2
   4..............2

 

te adjunto un archivo!

 

esperoq ue te sirva, salu2!!!

2013-04-20T22:28:15+02:00

g(0) = 0                  g`1(0) = No existe 
g(2) = 1                   g^-1(1) = 2
g(3) = 3/2                g^-1(2) = 1